MODELS, NORMS AND GOALS FOR ENGLISH AS AN INTERNATIONAL LANGUAGE PEDAGOGY AND TASK BASED LANGUAGE TEACHING AND LEARNING - WIDHIA NINSIANA (Premise: Journal of English Education and Applied Linguistics, 2012)
It is now a widely accepted phenomenon that English has spread to become a world language or a global lingua franca. Based on the increasing diversity in users and uses of English in crosscultural settings at the present time, the assumptions of current approaches in ELT are currently being reexamined in literature. This paper aims to examine the theoretical assumptions and practices of task based language teaching and learning within the framework of English as an international language pedagogy taking into consideration the issues of innovations in the nativization process, the use of native norms as a point of reference, the status of nonnative norms and the choice of a pedagogical model. Given the increasing importance of "mutual intelligibility" and "accommodation" in international interactions among English users from different backgrounds and of the studies in reconceptualization of competence in relation to EIL, the place of tasks in the curriculum is reexamined.